2004
DOI: 10.1176/appi.ps.55.12.1431
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving Attitudes and At-Risk Maternal Behavior Among Mothers With Major Mental Illness

Abstract: In an effort to improve parenting assessments for mothers with mental illness, this study examined the relationship between caregiving attitudes and maternal behavior. Participants included 44 mothers with major mental illness who were involved with the child welfare system and their young children. The Parenting Opinion Questionnaire (POQ) was administered to assess caregiving attitudes. Maternal behavior was assessed directly in a videotaped observation. Unrealistic maternal caregiving attitudes, especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 7 publications
0
22
0
6
Order By: Relevance
“…Similarly, for infants with low scores on the Cooperative scale, the remaining infant scales (Infant Compulsive, Infant Difficult, and Infant Passive) indicate the nature of this behaviour. The CARE index has been validated for use with families from different social classes and cultural backgrounds (Leventhal et al, 2004). The infant version was used in this study, which is appropriate from birth to 15 months (Crittenden, 2004).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, for infants with low scores on the Cooperative scale, the remaining infant scales (Infant Compulsive, Infant Difficult, and Infant Passive) indicate the nature of this behaviour. The CARE index has been validated for use with families from different social classes and cultural backgrounds (Leventhal et al, 2004). The infant version was used in this study, which is appropriate from birth to 15 months (Crittenden, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Maternal Sensitivity was chosen over 'Infant Cooperative' and PSI Parental Competence because adult sensitivity is the central construct within the CARE index (Crittenden, 2004), and of primary interest in this study. Additionally, there is precedence for using only this scale from the CARE index (Leventhal et al, 2004). Measures of maternal sensitivity have been included in many studies, with poorer maternal sensitivity repeatedly demonstrated in mothers with depression (Cohn et al, 1990, Murray et al, 1996 and with schizophrenia (Goodman & Brumley, 1990;Riordan et al, 1999).…”
Section: The Relationship Between Mother-infant Interaction and Cognimentioning
confidence: 99%
“…This procedure is based on short 3 to 5 minute videotaped free adult-infant play interactions. It has been validated for use with families from different social classes and cultural backgrounds (Leventhal, Jacobsen, Miller & Quintana, 2004) and shown to discriminate interactional patterns between abusive and non-abusive mothers and their infants (Cassidy et al, 1996). For each parent-infant dyad, seven aspects (facial expression, verbal expression, position, affection, turn-taking, control and choice of activity) were evaluated and contributed to scores on three adult scales (sensitive, controlling or unresponsive) and four infant scales (cooperative, difficult, compulsive and passive).…”
Section: Parent-infant Interactionsmentioning
confidence: 99%
“…Although different tasks or settings (e.g. diaper change, free play in the home) may have elicited different behaviors, prior research does support the validity of brief structured laboratory observations coded with similar global rating scales (Leventhal, Jacobsen, Miller, & Quintana, 2004; Shaw et al, 1998). …”
Section: Discussionmentioning
confidence: 99%